Impacts of Deoxygenation and Hypoxia on Shark Embryos Anti-Predator Behavior and Oxidative Stress - Varela, Jaquelino (2023)
The authors would like to thank the Prince Albert II of Monaco Foundation, Intergovernmental Panel on Climate Change (IPCC), and Camões—Instituto da Cooperação e da Língua, I.P. This research is part of project NGANDU funded by the Portuguese Foundation for Science and Technology (FCT) and the Aga Khan Development Network (AKDN) under grant agreement FCT AGA-KHAN/541746579/2019. This work was co-funded by Programa Operacional Regional de Lisboa, Portugal 2020 and the European Union within the project LISBOA-01-0145-FEDER-028609. All authors acknowledge funding from granted to MARE, project LA/P/0069/2020 granted to the Associate Laboratory ARNET, and project LA/P/0140/2020 of the Associate Laboratory Institute for Health and Bioeconomy—i4HB. Further, CS acknowledges the support from the project AGA-KHAN/541746579/2019, financed by FCT and the Aga Khan Development Network (AKDN), through Nova School of Business and Economics. FCT supported JRP through scientific employment stimulus program (2021.01030.CEECIND). TR was funded through an FCT researcher contract (DL57/2016/CP1479/CT0023). Publisher Copyright: © 2023 by the authors.